The Relationship Between Serum Vitamin D3 Levels and Recurrent Urinary Tract Infection in Children Aged 2-15 Years - Emami, Elham; Oroojeni, Atrin; Mansuri, Maryam (Journal of Pediatric Nephrology, 2025)
Background and Aim: Urinary tract infection (UTI) is one of the most common infectious diseases in children, which may cause certain complications, such as growth disorders, hypertension, proteinuria, and chronic kidney failure. In addition to vitamin D’s vital role in bone formation, it also contributes to the functioning of the immune system, and its low levels are associated with increased susceptibility to infections. Given the role of vitamin D in regulating the immune system, the present study was conducted to investigate the relationship between serum vitamin D levels and recurrent UTI in children. Methods: In this cross-sectional study, 90 children aged 2-15 years who were referred to the Pediatrics Department of Hajar Hospital, Shahrekord, in 2022 were included and divided into two groups: Cases (with UTI) and controls (not suffering from UTI). Children’s information was recorded and blood samples were collected to measure 25-hydroxyvitamin D3 levels. Data were analyzed using SPSS. Results: The groups showed no significant difference in age and gender (P>0.05). The groups showed a significant difference in the frequency of serum vitamin D levels (P<0.0001); vitamin D deficiency and insufficiency were more common in children with UTI compared to those without UTI (24.4% and 48.9% vs 8.9% and 15.6%, respectively). Conclusion: Vitamin D deficiency is correlated with UTI in children, and its supplements are a low-risk treatment of choice to prevent UTI.